Association of Anxiety With Pain and Disability but Not With Increased Measures of Inflammation in Adolescent Patients With Juvenile Idiopathic Arthritis. Issue 9 (23rd July 2020) - Hanns, Laura; Radziszewska, Anna; Suffield, Linda; Josephs, Francesca; Chaplin, Hema; Peckham, Hannah; Sen, Debajit; Christie, Deborah; Carvalho, Livia A.; Ioannou, Yiannis
Abstract : Objective: To explore whether anxiety and depression are associated with clinical measures of disease for adolescent patients with juvenile idiopathic arthritis (JIA) and whether anxiety and depression are associated with increased peripheral proinflammatory cytokine levels in adolescent patients with JIA and in healthy adolescent controls. Methods: A total of 136 patients with JIA and 88 healthy controls ages 13–18 years completed questionnaires on anxiety and depressive symptoms. For patients with JIA, pain, disability, physician global assessment (using a visual analog scale [VAS]), and number of joints with active inflammation (active joint count) were recorded. In a subsample, we assessed lipopolysaccharide‐stimulated interleukin 6 (IL‐6) production from peripheral blood mononuclear cells, serum IL‐6, cortisol, and C‐reactive protein levels. Data were analyzed by linear regression analysis. Results: Levels of anxiety and depressive symptoms in patients with JIA were not significantly different than those in healthy controls. For patients with JIA, anxiety was significantly associated with disability (β = 0.009, P = 0.002), pain (β = 0.029, P = 0.011), and physician global assessment VAS (β = 0.019, P = 0.012), but not with active joint count (β = 0.014, P = 0.120). Anxiety was not associated with any laboratory measures of inflammation for JIA patients. These relationships were also true for depressive symptoms. For healthy controls, there was a trend toward an association of anxiety (but not depressive symptoms) with stimulated IL‐6 (β = 0.004, P = 0.052). Conclusion: Adolescent patients with JIA experience equivalent levels of anxiety and depressive symptoms as healthy adolescents. For adolescent patients with JIA, anxiety and depressive symptoms are associated with pain, disability, and physician global assessment VAS, but not with inflammation.